Comprehensive Analysis of Evolutionary Characterization and Expression for Monosaccharide Transporter Family Genes in Nelumbo nucifera - Wu, Peng; Zhang, Yongyan; Zhao, Shuping; Li, Liangjun (Frontiers in Ecology and Evolution, 2021)
The sugar transporter, an important class of transporter for sugars function, play regulators of many processes associated with growth, maturation and senescence processes in plant. In this study, a total of 35 NNUSTs were identified in the Nelumbo nucifera genome. In addition, all NNUSTs genes identified were grouped by conserved domains and phylogenetic analysis. Additionally, we identified 316 ST genes in other 10 representative plants, and performed a comparative analysis with Nelumbo nucifera, including evolutionary trajectory, gene duplication, and expression pattern. A large-scale analysis across plants and alga indicated that the ST family could have been originated from STP and Glct, expanding to form STP and SFP by dispersed duplication. Finally, quantitative real-time polymerase chain reaction and cis-elements analysis showed that some of them might probably be regulated by plant hormones (e.g., salicylic acid, abscisic acid, and auxin), abiotic (e.g., drought, excessive cold, and light), and biotic stress factors. The experiment found that under the four abiotic stress conditions, only NNUSTP5 expression was up-regulated, generating stress response, and ARBE and LTR were present in NNUSTP5. In summary, our findings are significant in understanding and exploring the molecular evolution and mechanisms of NNUSTs in plants.